The complete mitochondrial genome of the Formosan black bear (Ursus thibetanus formosanus) - Tsai, Chi-Li; Chou, Yii-Cheng; Shih, Chih-Chin; Cheng, Hsi-Chi; Yang, Chieh-Chung; Kao, Hsiao-Wei (Zootaxa, 2009)
A complete mitochondrial genome of the Formosan black bear (Ursus thibetanus formosanus) was obtained by PCR amplification and DNA sequencing. The genome spans 17,044 bp that includes 13 protein-coding genes, 22 tRNA genes, and two rRNA genes. The base composition of the heavy strain is 31.0% A, 25.6% C, 15.7% G, and 27.7% T. The control region (CR) is located between tRNA-Pro and tRNA-Phe, consists of 1,595 bp, and comprises 9.4% of the whole genome. The DNA sequence shares 98.7%, 96.3%, 91.0%, 91.8%, and 91.7% similarity with those of U. t. thibetanus, U. t. mupinensis, U. americanus, U. arctos, and U. maritimus respectively. Phylogenetic analyses suggest that the Formosan black bear is more closely related to U. t. thibetanus than to U. t. mupinensis.